Empowering Youth and Women: Showcasing Innovative Sheep Fattening Practices in Amhara, Ethiopia - Ekule, Muluken; Wamatu, Jane; Belayneh, Tesfa; Bisrat, Asfaw (International Center for Agricultural Research in the Dry Areas, 2024)
In the heart of Basona Worena district of the Amhara Region in Ethiopia, a transformative narrative unfolded in the villages of Abamote and Gudoberet. A total of 150 determined young women and men, members of sheep fattening groups, arranged a two-day remarkable field days to showcase of their 90-day journey, culminating in the presentation of their market-ready sheep. The event did not only mark the demonstration of improved fattening practices but also heralded the beginning of an entrepreneurial culture in sheep fattening among the youth and women.